2012
DOI: 10.3109/09513590.2012.705377
|View full text |Cite
|
Sign up to set email alerts
|

Adnexal torsion in children and adolescents: new trends to conservative surgical approach – Our experience and review of literature

Abstract: The purpose of this study is to discuss the surgical treatment for ovarian torsion in children and adolescents with a focus on the procedures of adnexal conservation surgery and its frequency in the literature of the last 10 years. We retrospectively reviewed the medical charts of 127 operative ovarian lesions including 30 ovarian torsions (23.6%) treated in two pediatric centers over a 10-year period. Age at presentation, presenting symptoms, diagnostic studies, surgical procedure and pathological findings we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
1
7

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 92 publications
(72 citation statements)
references
References 46 publications
4
59
1
7
Order By: Relevance
“…1 The next common symptom in this study was nausea and vomiting seen in 37 (78.7%) cases similar to other studies. 11,14 In this study palpable mass was seen in 14 (29.7%) cases and tenderness was demonstrated only in 17 (36.1%) cases and was similar to another study. 12 Other symptoms like vaginal bleeding and urinary symptoms reported in other studies were not noted in this study.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…1 The next common symptom in this study was nausea and vomiting seen in 37 (78.7%) cases similar to other studies. 11,14 In this study palpable mass was seen in 14 (29.7%) cases and tenderness was demonstrated only in 17 (36.1%) cases and was similar to another study. 12 Other symptoms like vaginal bleeding and urinary symptoms reported in other studies were not noted in this study.…”
Section: Discussionsupporting
confidence: 89%
“…1,14,20 Normal adnexal appearance is common in 69% of premenarchal patients. 21 Some studies 9,20 show enlarged ovary with multiple peripheral follicles as sign of torsion with a sensitivity of 64-74%.…”
Section: 16mentioning
confidence: 99%
See 1 more Smart Citation
“…There were 50 cases (71.4%) between the sizes of 5-10 cm which had undergone torsion [Table/ Fig-3]. In about Our study Kandasami Vijayalakshmi et al, [7] C Spinelli et al, [14] Vijayaraghavan [15] 34 [48.6%] cases tumours was found to be a risk factor for torsion. 11 cases (15.7%) there was no risk factor for torsion.…”
Section: Discussionmentioning
confidence: 53%
“…Ultrasound was done in all the patients, which showed ovarian mass in 29 cases (72.5%), among which 14 cases were of mature teratoma, 10 were cyst adenoma, 2 cases of functional cysts, 2 cases of malignant neoplasm and 1 case had synchronous mature teratoma with carcinoma ovary. 28 presented a review of literature to discuss the management of ovarian torsion in children and adolescents. It was found that 76.7% cases were associated with underlying pathology, of which 56.7% had functional ovarian lesion and 20% had benign neoplasm while in remaining 23.3% cases ovarian torsion was found with normal adnexa.…”
Section: Ovarian Torsionmentioning
confidence: 99%